Differential toxin profiles of ciguatoxins in marine organisms: Chemistry, fate and global distribution. (August 2018) - Soliño, Lucía; Costa, Pedro Reis
Abstract: Ciguatoxins (CTXs) are fish metabolism products and a result of biotransformation of precursor gambiertoxins produced, in the first instance, by benthic dinoflagellates Gambierdiscus and Fukuyoa . Ciguatoxins are potent neurotoxins that selectively open voltage gated sodium channels in excitable cells causing the human food poisoning known as Ciguatera (CFP). Endemic from tropical areas in central Pacific and West Indian Ocean, and the Caribbean Sea, CTX may affect up to 500, 000 people annually due to fish consumption. Their recent occurrence in European waters highlights the need for a multidisciplinary approach of CTX research in order to better understand the diversity and transformation of microalgae products through food webs. This article intends to review available information on chemistry, toxicity, distribution and fate of known CTX compounds from a critical perspective to provide an overview of future trends and needs on ciguatera research. Highlights: A comprehensive overview on fish and microalgae CTX profiles is presented. Regional and species-associated toxin profiles are described. Fish feeding and metabolic pathways leading to CTX accumulation are discussed.